Patterns and Correlates of Nurse Departures From the Health Care Workforce: Results From a Statewide Survey. Issue 5 (6th May 2023) - Medvec, Barbara R.; Marriott, Deanna J.; Khadr, Lara; Ridge, Laura J.; Lee, Kathryn A.; Friese, Christopher R.; Titler, Marita G.
Abstract : Background: Health care executives and policymakers have raised concerns about the adequacy of the US nursing workforce to meet service demands. Workforce concerns have risen given the SARS-CoV-2 pandemic and chronically poor working conditions. There are few recent studies that directly survey nurses on their work plans to inform possible remedies. Methods: In March 2022, 9150 nurses with a Michigan license completed a survey on their plans to leave their current nursing position, reduce their hours, or pursue travel nursing. Another 1224 nurses who left their nursing position within the past 2 years also reported their reasons for departure. Logistic regression models with backward selection procedures estimated the effects of age, workplace concerns, and workplace factors on the intent to leave, hour reduction, pursuit of travel nursing (all within the next year), or departure from practice within the past 2 years. Results: Among practicing nurses surveyed, 39% intended to leave their position in the next year, 28% planned to reduce their clinical hours, and 18% planned to pursue travel nursing. Top-ranked workplace concerns among nurses were adequate staffing, patient safety, and staff safety. The majority of practicing nurses (84%) met the threshold for emotional exhaustion. Consistent factors associated with adverse job outcomes include inadequate staffing and resource adequacy, exhaustion, unfavorable practice environments, and workplace violence events. Frequent use of mandatory overtime was associated with a higher likelihood of departure from the practice in the past 2 years (Odds Ratio 1.72, 95% CI 1.40–2.11). Conclusions: The factors associated with adverse job outcomes among nurses—intent to leave, reduced clinical hours, travel nursing, or recent departure—consistently align with issues that predated the pandemic. Few nurses cite COVID as the primary cause for their planned or actual departure. To maintain an adequate nursing workforce in the United States, health systems should enact urgent efforts to reduce overtime use, strengthen work environments, implement anti-violence protocols, and ensure adequate staffing to meet patient care needs.